2017
DOI: 10.4490/algae.2017.32.8.14
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of inflammatory responses elicited by urban fine dust particles in keratinocytes and macrophages by diphlorethohydroxycarmalol isolated from a brown alga Ishige okamurae

Abstract: Fine dust (FD) particles have become a major contributor to air pollution causing detrimental effects on the respiratory system and skin. Although some studies have investigated the effects of FD on the respiratory system, their possible effects on the skin remain under-explored. We investigated the FD mediated inflammatory responses in keratinocytes, present in the outer layers of skin tissues and the transfer of inflammatory potential to macrophages. We further evaluated the anti-inflammatory effects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Many studies have been conducted to find the bioactive extracts or active ingredients derived from natural sources, particularly having polyphenol structure including hydroxyl groups on aromatic rings, which can modulate the generation of UVB induced-ROS (Samarakoon et al 2013, Farooqi et al 2015, Lee et al 2015b, 2015c, 2015d, Alves et al 2016, Fernando et al 2017a, 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to find the bioactive extracts or active ingredients derived from natural sources, particularly having polyphenol structure including hydroxyl groups on aromatic rings, which can modulate the generation of UVB induced-ROS (Samarakoon et al 2013, Farooqi et al 2015, Lee et al 2015b, 2015c, 2015d, Alves et al 2016, Fernando et al 2017a, 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PM causes epithelium damage, and endothelial dysfunction has been reported previously [8,9,38]. PM induce skin damages or diseases mainly through stimulating inflammatory response and oxidative stress [5,39]. Ryu et al investigated that PM induced epidermic inflammatory response in human keratinocytes [39].…”
Section: Discussionmentioning
confidence: 97%
“…In general, PM were produced by human activity, such as chemical production and fossil fuel combustion [1,2]. PM are related to various diseases, including inflammations such as skin inflammation and lung inflammation, kidney diseases such as chronic kidney disease and end-stage renal disease, metabolic syndromes such as diabetes and obesity, as well as skin aging such as wrinkle formation [3][4][5][6][7][8][9][10][11]. Skin is the largest organ in humans and the primary organ exposed to PM.…”
Section: Introductionmentioning
confidence: 99%
“…Fernando et al [47] reported for the first time the use of a zebrafish embryo model for evaluating the inflammatory effects of fine dust (FD) particles, which are a major aggressive agent in air pollution. The authors determined that a concentration of 48.8 µM of 3 significantly decreased NO and ROS production and prevented fine dust inflammation-induced cell death [47].…”
Section: Diphlorethohydroxycarmalolmentioning
confidence: 99%
“…Fernando et al [47] reported for the first time the use of a zebrafish embryo model for evaluating the inflammatory effects of fine dust (FD) particles, which are a major aggressive agent in air pollution. The authors determined that a concentration of 48.8 µM of 3 significantly decreased NO and ROS production and prevented fine dust inflammation-induced cell death [47]. The effect of 3 against high glucose-induced angiogenesis in zebrafish embryos was studied, and it was found that the treatment of embryos with a concentration of 2 µM of 3 suppressed high glucose-induced dilation in the retinal vessel diameter and vessel formation ( Table 1).…”
Section: Diphlorethohydroxycarmalolmentioning
confidence: 99%